The Weight of a Heavy Hour: Understanding Teacher Experiences of Work Intensification - Beck, Jaime (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2017)
The teachers in this study identified the experiences related to increases in the intensity of teachers’ work to be a misunderstood and under-discussed aspect of the profession. During research conversations that took place in the context of a year-long narrative inquiry, the term heavy hours was coined to describe these experiences. The salient features of heavy hours described include: rapid professional decision-making, being pulled in an excess of directions, and the residue that lingers long after the hour is over. After exploring the ways in which the teachers in this study experienced and defined heavy hours, this paper asserts that foregrounding this understanding has implications for the way in which we prepare and support teachers throughout their careers.